Voices of other publics: online magazines, Africa is a country and vanguard as a representation of alternative media in democratic South Africa - Zuma, Nontebeko (My University, 2017)
This paper evaluates the ways in which online magazines, Africa is a Country and Vanguard, are representative of alternative media in democratic South Africa. It frames its arguments within the prevailing discursive democratic theory of the counterpublic sphere and examines how these publications’ choice of content production, editorial contributors, target audiences and participatory norms characterise them as such a space. The study argues that as platforms of critical deliberation on issues based on the ideological beliefs, interests and lived experiences of their participants, these media can be regarded as counterpublics existing on the margins of conventional media. As a consequence of their exclusion from the consciousness of 'dominant publics', their publishing activities tend to counter or be of contestatory editorial positioning as a challenge to mainstream media. This study advances that their production of critical content, representation of (and as) marginalised voices and their contribution to public deliberation contribute to our understanding of the role of alternative media in democratic South Africa. To further understand the critical nature of their coverage, this thesis also interrogates Africa is a Country and Vanguard’s socio-political content, by analysing their reports of the Rhodes Must Fall1 discourse which saw student uprisings around the issue of transformation in South Africa’s institutions of higher learning; as well as the xenophobic attacks that put the country in the global spotlight in 2015.
A thesis submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in fulfillment of the requirements for the degree of Masters of Journalism and Media Studies. January 2017
Keywords: Alternative mass media; Mass media--Social aspects; Alternative mass media--Economic aspects